The Impact of Work-Life Balance on Job Satisfaction, Job Performance, and Workplace Engagement Among Generation Z Employees: A Comprehensive Analysis - Septian; Dimas; Dwi; Irma; Muhammad; Refiana; Vian; Nurkholish (PROSENAMA, 2024)
This research explores the impact of work-life balance on job satisfaction, job performance, and workplace engagement among Generation Z employees. As this cohort increasingly enters the workforce, understanding their unique expectations regarding work-life integration becomes essential for organizations aiming to enhance employee outcomes. A literature review reveals a consistent positive correlation between work-life balance and job satisfaction, with studies indicating that employees who perceive a favorable work-life balance report higher levels of job satisfaction and engagement. For instance, research by highlights that work-life balance significantly influences job satisfaction and performance among both Millennials and Generation Z (Waworuntu et al., 2022). Furthermore, the findings suggest that work-life balance not only enhances job satisfaction but also positively impacts job performance, as evidenced by studies indicating that supportive workplace policies and flexibility are crucial for fostering engagement (Bataineh, 2019; Thakur & Madhu, 2019). However, limitations in the existing literature, such as reliance on self-reported measures and a lack of longitudinal studies, suggest the need for further research to validate these findings across diverse contexts. Recommendations for future studies include exploring the effects of work-life balance in various industries and cultural settings, as well as implementing comprehensive work-life balance initiatives to improve employee engagement and organizational performance. This research underscores the importance of prioritizing work-life balance to foster a productive and satisfied workforce, particularly among Generation Z.